Humanisasi Teknologi dalam Pendidikan: Analisis Filsafat Terhadap Ancaman Dehumanisasi di Era Pembelajaran Digital Berbasis AI - Nihayatus Sholihah; Ari Abi Aufa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The rapid digital transformation occurring in the field of education, particularly through the integration of artificial intelligence (AI), has created new opportunities for improving learning efficiency, personalizing instruction, and supporting educators’ workloads. However, these advancements also bring forth significant philosophical challenges, especially the potential for dehumanization within the educational process. This article examines how technology influences the fundamental human dimensions of learning and how the concept of humanization can serve as an ethical framework for designing and implementing educational technologies. AI-based digital learning environments often position learners as data objects, reducing the dialogical, empathetic, and relational aspects that are fundamental to humanistic education. Drawing on philosophical perspectives from existentialism and humanism, this study evaluates the potential threats to student autonomy, critical thinking, and character formation. Furthermore, it explores how the human–technology relationship can be ethically framed through the theory of technological mediation and Paulo Freire’s notion of liberatory education. The analysis indicates that technology can be humanized by emphasizing meaningful interaction, ensuring algorithmic transparency, and strengthening the role of teachers as mediators of values and empathy. Ultimately, the article argues that the benefits of AI in education can only be fully realized when technological development and implementation are guided by an ethical orientation that places human beings at the center. This study contributes to ongoing discussions on the role of technology in education and provides a critical perspective aimed at minimizing the risk of dehumanization in an era increasingly shaped by AI-driven digital learning.